The Factors Affecting Brand Associations of the Iranian Football League Organization - Rasoul Tarighi; Niloofar Pashaklaei; Maliheh Salehi Rostami; Azim Salahi Kojour (Shahid Bahonar University of Kerman, 2021)
Branding is the main process of profitability and it can be defined as critical basis for sport industry. Therefore, the purpose of this study was to analyze the factors affecting the brand associations of the Iranian football league organization. The research population of the study included the faculty members of universities, members of the board of directors of the football federation, the board and staff of the league organization, and the managers and experts of the football federation. The research sample was selected through convenience sampling. A researcher-developed questionnaire was distributed for collecting the research data. The validity of the questionnaire was confirmed by ten professors of sports management and the reliability was confirmed using Cronbach's alpha test. To analyze the research data, Partial Least Squares test (PLS) was applied. Findings showed that the research variables included tradition, competitive balance, stadium atmosphere, management, competition, star player, education, competition, game show, community pride, socialization, player development, getting rid of everyday life, nostalgia, interest in a special team, excitement, acceptance in the peer group, logo, and product delivery had a positive and significant effect on the brand associations of Iranian football league organization. Therefore, it is suggested that managers and officials of sports federations use the results of this research to enhance the brand positioning of the football leagues.